Penggunaan Google Form Sebagai Media Pengumpulan Tugas Siswa Kelas XI TKJ Di SMK Negeri 1 Kendit - Fuad Burhanul Bulqiah (Edukasi Elita : Jurnal Inovasi Pendidikan, 2024)
: How to achieve good learning outcomes and stimulate students to be more creative and innovative in developing their cognitive aspects and creating an academic atmosphere in teaching and learning activities requires harmonious and scientific cooperation. So the step taken to provide innovation in learning is to use Google Forms as a medium for assigning assignments. In this research, researchers are in line with previous research and will focus on learning by implementing the use of Google forms as a medium for giving assignments to class XI TKJ students at SMK Negeri 1 Kendit. This research uses a qualitative descriptive method. The results of this research are that using Google Forms to provide assignments provides interactive benefits for educators and students.